HIMENÓPTEROS PARASITÓIDES (INSECTA, HYMENOPTERA) EM ÁREA AGRÍCOLA DE RIO CLARO, SP, BRASIL - Souza, L.; Braga, S.m.p. [UNESP]; Campos, M.j.o. [UNESP] (Instituto Biológico, 2022)
From May 2003 to June 2004, collections were made using the Moericke trap placed in an agricultural area in Rio Claro (22º20’S, 47º32’O), SP, Brazil, resulting in the capture of a total of 5,308 specimens of parasitoids, belonging to 8 superfamilies and 22 families. Mymaridae, Encyrtidae, Scelionidae and Platygastridae were the most common families, being responsible for 30.88%, 19.05%, 14.96% and 6.69% of the total number of parasitoids collected, respectively. Another 18 families were present with relative frequency lower than 5%.

Entre maio de 2003 e junho de 2004 foram coletados, com armadilha de Moericke, no Município de Rio Claro (22º20’S, 47º32’O), SP, Brasil, 5.308 indivíduos de himenópteros parasitóides pertencentes a 8 superfamílias e 22 famílias. As famílias Mymaridae, Encyrtidae, Scelionidae e Platygastridae foram as mais comuns, com freqüência relativa de 30,88%, 19,05%, 14,96% e 6,69%, respectivamente, com relação ao total de parasitóides coletados. As demais 18 famílias foram coletadas em freqüência menor do que 5%.
PARASITOID HYMENOPTERA (INSECTA) COLLECTED IN AN AGRICULTURAL AREA IN RIO CLARO, SP, BRAZIL
Keywords: Agroecosystem; Hymenoptera; parasitoids; Survey; Moericke trap; Agroecossistema; Hymenoptera; Parasitóides; Levantamento; Armadilha Moericke